In horses with trigeminal-mediated headshaking, is neuromodulation with EquiPENS™ more effective than with electroacupuncture? - Hindmarsh, Jennifer (Veterinary Evidence, 2021)
PICO question In horses diagnosed with trigeminal-mediated headshaking, is EquiPENS™ therapy more efficacious when compared to electroacupuncture in terms of remission of clinical signs? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Three papers were critically reviewed, all three were descriptive case series Strength of evidence Weak Outcomes reported Remission was achieved following both EquiPENS™ and electroacupuncture therapy in a proportion of horses for variable lengths of time. Median remission times appear to be longer with repeated treatment of EquiPENS™ compared to electroacupuncture Conclusion The evidence for EquiPENS™ treatment is more robust than for electroacupuncture, and remission defined more clearly, and so could be recommended with greater confidence How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.